PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN BERKELANJUTAN BIDANG KEBUDAYAAN - Ludovikus Bomans Wadu (Jurnal Ilmiah Mimbar Demokrasi, 2016)
This research is done based on the phenomenon among the citizen of Lamaholot in converting the elephant’s trunk (Gading Gajah- GG) as Belis into the other form. Phenomenological study was applied in this research with qualitative approach which focused on portraying the participation of the citizen in the sustainable development. Main problems in this research were formulated into some research questions, such as 1) How do the perceptions of the citizen of Lamaholot on the conversion of GG as Belis into the other form? 2) How are the participation of the citizen of Lamaholot in the sustainable development? Data were collected through observation, interview and document analysis. The results show that 1) the perceptions of the citizen of Lamaholot on the conversion of GG as Belis is to preserve culture, 2) the form of citizen participation is reducing the number of prosecutions of the use of GG as well as converting it into the other form. This citizen action taken to support the concept of sustainable development because they are wise in making decisions.